Climate Change Impacts on Storage and Water Yield in Subtropical Environment: Hydrological Modeling and Uncertainty Analysis - Siefert, Cesar Augusto Crovador; Marangon, Fernando Helmuth Syring; Santos, Irani dos (Sociedade & Natureza, 2018)
Impacts of climate change scenarios on water storage and streamflow generation processes in subtropical catchments are partially described and understood. The hydrologic conceptual model HBV-Light was applied to understand storage dynamic and water yield caused by climate changes and the modelling uncertainty at the Pequeno River Catchment, PR. Climate change scenarios A2 and B2 from IPCC-SRES were used to simulate catchment behaviour over the period 2071-2100 and were compared to baseline period (1981-2010). Daily data were used for the calibration period and provided a good model fit (NSE ≥ 0,7) for calibration and validation periods. The uncertainty ranges were substantially lower than the increase in storage variation and water yield induced by climate change scenarios. The results showed a significant increase in soil water storage on and groundwater. However the water deficit in soil and groudwater for A2 and B2 is lower, a greater volume of water avaliable to become runoff is expected. The results indicated an increase on overland and subsurface flow for the scenarios, demonstrating a possible change on the streamflow generation processes in Pequeno River Cathcment